Weaning calves early from drylot - M. McKee; G. Fink (Kansas Agricultural Experiment Station Research Reports, 1978)
Percentage Simmental and Hereford calves gained slightly more (13 lbs./hd) while nursing their mothers than 83 herd mates that were weaned early at 49 (+27) days of age. Percentage Simmental cows whose calves were weaned early had a higher conception rate than percentage Simmental cows that nursed calves (93% vs. 89%) Dams of calves weaned early rebred 17.6 days sooner than nursing dams.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Weaning calves; Drylot; Conception rate